Balance training for neuromuscular control and performance enhancement: A systematic review - Zech, A.; Hübscher, M.; Vogt, L.; Banzer, W.; Hänsel, F.; Pfeifer, K. (Journal of Athletic Training, 2010)
Objective: As a result of inconsistencies in reported findings, controversy exists regarding the effectiveness of balance training for improving functional performance and neuromuscular control. Thus, its practical benefit in athletic training remains inconclusive. Our objective was to evaluate the effectiveness of training interventions in enhancing neuromuscular control and functional performance.